Byzantium : from Antiquity to the Renaissance - Mathews, Thomas F. (London Yale University Press, 1998)
With images culled from eleven hundred years of history, this title explores the Byzantine empire's vast range of artistic splendours that informed the art of modern Europe. It emphasizes that the Byzantines' interest in humanism and painting the human figure became the essential bridge between classical and renaissance Europe.
Include Colour Illustrations, Bibliography and Index
Keywords: Art, Byzantine -- Byzantine Empire -- Civilization